Targeting adverse effects of antiseizure medication on offspring: current evidence and new strategies for safety. (1st February 2023) - Sha, Leihao; Yong, Xihao; Shao, Zhenhua; Duan, Yifei; Hong, Qiulei; Zhang, Jifa; Zhang, Yunwu; Chen, Lei
ABSTRACT: Introduction: For women with epilepsy of reproductive age, antiseizure medications (ASMs) are associated with an increased risk of offspring malformations. There are safety concerns for most anti-seizure medications in the perinatal period, and there is a clear need to identify safe medications. ASMs must transport through biological barriers to exert toxic effects on the fetus, and transporters play essential roles in trans-barrier drug transport. Therefore, it is vital to understand the distribution and properties of ASM-related transporters in biological barriers. Areas covered: This study reviews the structure, transporter distribution, and properties of the blood-brain, placental, and blood-milk barrier, and summarizes the existing evidence for the trans-barrier transport mechanism of ASMs and standard experimental models of biological barriers. Expert opinion: Ideal ASMs in the perinatal period should have the following characteristics: 1) Increased transport through the blood-brain barrier, and 2) Reduced transport of the placental and blood-milk barriers. Thus, only low-dose or almost no antiseizure medication could enter the fetus's body, which could decrease medication-induced fetal abnormalities. Based on the stimulated structure and molecular docking, we propose a development strategy for new ASMs targeting transporters of biological barriers to improve the perinatal treatment of female patients with epilepsy.